The University of Genova Climate Policies - Delfino, Federico; Borghi, Adriana Del; Laiolo, Paola; Marin, Valentina; Spotorno, Stefano; Gallo, Michela (Journal of Sustainability Perspectives, 2025)
The University of Genova (UniGe) has undertaken a significant commitment against climate change, with the goal of becoming climate neutral by 2030. The commitment began in 2014 with the calculation of its carbon footprint and has developed through several stages. In 2019, it joined "The Sustainable Development Goals Accord" and declared a Climate Emergency, also joining the United Nations' "Race To Zero for Universities and Colleges" campaign. In 2022, it approved its Climate Neutrality Strategy 2022-2030, and in 2025, it will implement its Climate Action Plan. UniGe's Climate Action Plan includes two main sections: mitigation and adaptation. The mitigation plan, based on annual greenhouse gas (GHG) inventory, outlines the path to climate neutrality, with intermediate and long-term goals to reduce direct emissions (from fossil fuels), indirect emissions linked to energy consumption, and indirect emissions related to mobility, waste, water consumption, and procurement. Residual emissions will be offset through the purchase of certified credits. The adaptation plan aims to increase UniGe's resilience to climate change: it is based on the Liguria Region strategy, integrated with internal policies and procedures for risk management (weather alerts, hydrogeological risks, exposure to extreme temperatures, etc.) and actions for educating and raising awareness within the academic community.